The Role of Indonesian Government Policy in Shaping the Competitive Landscape of the Southeast Asian Beauty Industry - Hasrudin, Trya; Sagena, Uni (Research Horizon, 2023)
This research aims to elucidate the strategies implemented by the Indonesian Government to promote the expansion of the beauty industry in the Southeast Asian market. The Indonesian beauty industry has proven resilient in the face of pandemic conditions and has contributed significantly to the Indonesian economy. Consequently, the Indonesian Government is actively pursuing policies and providing assistance to facilitate the industry's expansion into the Southeast Asian market. The research employs an explanatory research methodology, utilizing both secondary data sources and primary data gathered from journals, theses, news articles, and interviews with officials from the Ministry of Industry. The fundamental theoretical framework employed in this study is based on Richard C. Snyder's decision-making model. Through this theoretical lens, the research findings reveal that the policies and assistance offered by the Indonesian Government are influenced by a combination of internal and external factors, both of which hold equal significance and influence one another during the decision-making process. Furthermore, social structure and behavior are interrelated and exert mutual influence within the realm of internal factors..